The β-hairpin of 40S exit channel protein Rps5/uS7 promotes efficient and accurate translation initiation in vivo - Jyothsna Visweswaraiah; Yvette Pittman; Thomas E Dever; Alan G Hinnebusch (eLife, 2015)
The eukaryotic 43S pre-initiation complex bearing tRNAiMet scans the mRNA leader for an AUG start codon in favorable context. Structural analyses revealed that the β-hairpin of 40S protein Rps5/uS7 protrudes into the 40S mRNA exit-channel, contacting the eIF2∙GTP∙Met-tRNAi ternary complex (TC) and mRNA context nucleotides; but its importance in AUG selection was unknown. We identified substitutions in β-strand-1 and C-terminal residues of yeast Rps5 that reduced bulk initiation, conferred ‘leaky-scanning’ of AUGs; and lowered initiation fidelity by exacerbating the effect of poor context of the eIF1 AUG codon to reduce eIF1 abundance. Consistently, the β-strand-1 substitution greatly destabilized the ‘PIN’ conformation of TC binding to reconstituted 43S·mRNA complexes in vitro. Other substitutions in β-hairpin loop residues increased initiation fidelity and destabilized PIN at UUG, but not AUG start codons. We conclude that the Rps5 β-hairpin is as crucial as soluble initiation factors for efficient and accurate start codon recognition.